2018
DOI: 10.1016/j.bbapap.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of irreversible inhibition of Mycobacterium tuberculosis shikimate kinase by ilimaquinone

Abstract: Ilimaquinone (IQ), a marine sponge metabolite, has been considered as a potential therapeutic agent for various diseases due to its broad range of biological activities. We show that IQ irreversibly inactivates Mycobacterium tuberculosis shikimate kinase (MtSK) through covalent modification of the protein. Inactivation occurred with an apparent second-order rate constant of about 60 M s. Following reaction with IQ, LC-MS analyses of intact MtSK revealed covalent modification of MtSK by IQ, with the concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Because this moiety is critical for their binding to the ATP binding site of heat shock protein 90 (Hsp90), radicicol and M77976 also inhibit the kinase activity of Hsp90 [34,39]. Although IQ does not have the resorcinol moiety, it has been reported to be an inhibitor of other enzymes, including Mycobacterium tuberculosis shikimate kinase, S-adenosylhomocysteine hydrolase, DNA polymerase β, and M-phase inducer phosphatase 2 [25,40,41]. It is well known that some natural products exert activities on multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…Because this moiety is critical for their binding to the ATP binding site of heat shock protein 90 (Hsp90), radicicol and M77976 also inhibit the kinase activity of Hsp90 [34,39]. Although IQ does not have the resorcinol moiety, it has been reported to be an inhibitor of other enzymes, including Mycobacterium tuberculosis shikimate kinase, S-adenosylhomocysteine hydrolase, DNA polymerase β, and M-phase inducer phosphatase 2 [25,40,41]. It is well known that some natural products exert activities on multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…Among marine organisms, marine sponges produce several secondary metabolites, including quinones, steroids, alkaloids, terpenoids, and fatty acids, some of which possess drug-like characteristics [10]. Ilimaquinone (IQ), a sesquiterpene quinone isolated from marine sponges, exhibits a variety of biological activities, including anti-inflammatory [11], antitubercular [12], anti-HIV [13], and anti-tumor [14]. Previous studies have revealed that IQ interferes with protein transport by damaging the Golgi apparatus in cervical cancer cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several merosesquiterpenes are biologically active. For example, ilimaquinone ( 1 ) is cytotoxic against various cancer cell lines, with IC 50 values in a range of 0.5–25 μM, and has shown other related activities including anti-HIV and antituberculosis activities. , …”
mentioning
confidence: 99%